Armed Banditry and Terrorism in Northwest Nigeria: Interrogating the Legal, Ethical and Security Strategies (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
In recent years armed banditry is fast becoming a new normal life in Nigeria and the Northwest regions security challenges in particular has rapidly risen into a theatre of wars and this has triggered the movement of illicit activities of terrorists groups into the North Central region of the country. This paper examined the growing incidence of armed banditry and how it affected human security in the North West geographical zone of Nigeria with the view to ascertaining a sustainable roadmap to tackling armed banditry, kidnapping and insurgency in Nigeria. The study is methodologically structured using the doctrinal approach in data collection and this has to do with both primary and secondary sources. Research findings revealed that deployment of aerial and techno-driven surveillance, strengthened collaborative efforts of security agencies and telecom operators, a robust adoption of community participatory policing strategy can significantly minimize criminal activities in the affected region. Its findings equally found that armed banditry is driven by unemployment among youths, political interest by politicians, porous international borders and poverty among others. The paper submitted that, banditry insurgency and kidnapping within the region requires a multipronged approaches with both the municipal and international community working in collaboration to overcome the armed groups, protect the population across the vast ungoverned territory and exterminate the nexus of jihadist network and to dislocate the probable plans of the Islamic insurgencies in the central Sahel as well as the decade old Boko Haram insurgencies in the  lake Chad region of North West Nigeria..